Age-specific testosterone thresholds: reconsidering diagnostic criteria for hypogonadism across generations of Vietnamese men - Bac Nguyen Hoai; Thanh Do Truong; Thang Nguyen Cao; Quan Pham Minh; Vu Nguyen Bui Duy (The Aging Male)
The definition and diagnosis of functional hypogonadism (FH) remains challenging due to the nonspecific nature of symptoms and the inconsistency in normal testosterone thresholds. We conducted this single-center cross-sectional study on medical records of men aged 18 and above undergoing annual health check-ups to evaluate the correlation of age and metabolic components with testosterone. A total of 5,374 healthy men were included in the analysis. Total testosterone levels peaked at 18 years and gradually declined to age 40, followed by a mild increase. Based on the American Urology Association guideline, age-specific cutoffs for low testosterone were 14.61 nmol/l, 12.74 nmol/l, 12.70 nmol/l, and 13.98 nmol/l for those under 30, 30-40, 40-50, and over 50 years old respectively. Triglyceride - Glucose index showed a consistent negative correlation with testosterone across all age groups. In conclusion, testosterone levels demonstrated an age-related decline in early adulthood but a potential increase thereafter among healthy Vietnamese men. Metabolic components, rather than aging, had a consistent negative correlation with testosterone. Age-specific cutoffs for low testosterone may improve the detection of functional hypogonadism.